The concept of the digital therapeutic garden and its psychological effects - Lee, Jisoo; Yang, Yeji; Pyo, Ji-Eun; Kim, Ye-Seul; Choi, Kee-Hong; Kang, Shin-Koo; Nam, Su-Hwan; Song, Yu-Jin; Jeoun, Bu-Gi; Park, Sung-Hee (Frontiers in Psychology, 2025)
IntroductionTherapeutic gardens have been discussed as effective social interventions for promoting physical and mental health, and integrating digital technologies into therapeutic gardening offers a promising approach to enhance both accessibility and effectiveness. This study aimed to explore various forms of digital therapeutic gardening. Furthermore, it sought to investigate perceptions regarding digital therapeutic gardens and to examine the relationship between participation in such gardens and mental health.MethodsSurvey data were collected from 335 community-dwelling adults in Korea using across-sectional design. Demographic information and experiences with digital gardens were collected, and mental health variables including depression, anxiety, stress, vitality, life satisfaction, loneliness, and social networks were assessed. To investigate differences in mental health by experience with digital therapeutic gardens, t-tests and ANCOVA were performed.ResultsParticipants with experience in digital therapeutic gardens reported social, psychological, and physical benefits. They also demonstrated significantly higher levels of life satisfaction and vitality than those without such experience.DiscussionThis study highlights the potential therapeutic benefits of digital gardens and suggests that, when integrated with community gardens and mental health services, they may serve as a promising candidate for evidence-based interventions.